POLITICAL PARTIES AND GOVERNMENT BODIES (Scientific journal of the Fergana State University, 2023)
The author analyzes the concept of political party, and its role in society, as well as the functions of parties as an institution for the formation of government bodies. Also he expresses his views and assessments of the current problems in the party system in Uzbekistan and their solutions.